The Roles of BANKZISKA In Reducing Ribawi Practices in Society - Fery Setiawan; Riyanto, Riyanto (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
This study explores the roles of a productive entity owned by the Muhammadiyah agency for Amil, Zakat and Infaq services (LAZISMU) that is addressed with BANKZISKA. While it stands for financial assistance based on funds retrieved from Zakat, Infaq and Shodaqoh and other social, religious funds, it is a non-bank financing agency that aims to solve ribawi issues that are massively practised by Society. The purpose of this study is to analyze the strategies and activities of BankZiska to decrease the amount of Society ribawi practices. Taking place in the BankZiska branch in Magetan, East Java, this study uses a qualitative method with a descriptive approach. The data utilized is primary data obtained from informants and other sources. The findings show that BankZiska deploys the Qardhul Hasan system as the core of their activities, which focus on concessional lending without interest, Sharia economics literacy as well as entrepreneurship and other in-depth knowledge of the religion.